PEG/ZnBr2-Assisted Multicomponent Reactions: A Novel Procedure for the Synthesis of Functionalized 5,6-Dihydropyran-2-ones - Khalaj, Mehdi; Farahani, Nasrin; Sadeghpour, Mahdieh; Rajabzadeh, Halimeh; Khatami, Seyed Mola (Synlett, 2018)
We report a catalytic multicomponent reaction of isocyanides, oxiranes, and malonates under mild conditions, allowing the transformation of a wide range of substrates into 5,6-dihydropyran-2-one products in acceptable yields. We have also examined the leaving group selectivity using an unsymmetrical malonate. This novel method demonstrates the benefits of combining different activation modes in oxiranes.
Keywords: 5,6-dihydropyran-2-ones; PEG-400; oxiranes; isocyanides; malonates; catalytic multicomponent reactions